Powieść kryminalna Karin Slaughter "Zaślepienie" jako thriller medyczny z amerykańskiego Południa - Martynuska, Małgorzata (Wydawnictwo Uniwersytetu Rzeszowskiego, 2023)
The forensic thriller has emerged as a significant subgenre of crime fiction that depicts the work of medical examiners, coroners, forensic pathologists, and anthropologists who analyze scientific evidence. Forensic investigators do not engage directly in pursuing the criminal; instead, they interpret the physical evidence collected from the victim's body and the crime scene. The popularity of forensic fiction, film, and TV series has created the general assumption that criminalistics has become a routine police procedure. This article presents Karin Slaughter's novel Blindsighted as an example of the Southern forensic thriller. The American writer Karin Slaughter is the author of crime stories and thrillers set in the American South. Her Grant County series consists of six crime novels, beginning with Blindsighted and followed by Kisscut, A Faint Cold Fear, Indelible, Faithless, and Beyond Reach. The essay introduces the main qualities of a forensic thriller and highlights the novel's generic characteristics. Then, Blindsighted is analyzed within the paradigm of Southern regional literature, with its distinctive qualities and religious imagery.

Thriller medyczny stanowi podgatunek kryminału przedstawiający pracę lekarzy sądowych, koronerów, patologów i antropologów, analizujących dowody naukowe. Śledczy sądowi nie włączają się bezpośrednio w ściganie przestępców, a jedynie badają dowody zebrane z ciał ofiar i miejsc zbrodni. Popularność powieści, filmów i seriali z gatunku thrillera medycznego wpłynęła na przekonanie o stosowaniu kryminalistyki w rutynowych procedurach policyjnych. Niniejszy artykuł analizuje powieść Zaślepienie (2002), autorstwa Karin Slaughter, jako przykład regionalnego thrillera medycznego. Pisarka amerykańska Karin Slaughter jest autorką kryminałów i thrillerów, których miejscem akcji jest amerykańskie Południe. Seria Hrabstwo Grant składa się z sześciu powieści: Zaślepienie, Płytkie nacięcie, Zimny strach, Fatum, Niewierny, Przywilej skóry. Artykuł przedstawia charakterystykę thrillera medycznego i podkreśla przynależność gatunkową powieści Zaślepienie. Następnie analizuje powieść w kontekście specyfiki literatury regionalnej amerykańskiego Południa.
Karin Slaughter’s Crime Novel "Blindsighted" as a Southern Forensic Thriller
Keywords: crime fiction; forensic thriller; scientific evidence; American South; kryminał; thriller medyczny; dowód naukowy; amerykańskie Południe